2016
DOI: 10.1002/adhm.201600055
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ Gelling Drug Delivery System for Improved Recovery after Spinal Cord Injury

Abstract: Therapeutic strategies for the spinal cord injury (SCI) are limited by the current available drug delivery techniques. Here, an in situ gelling drug delivery system (DDS), composed of a Poloxamer-407, a 188 mixture-based thermoresponsive hydrogel matrix and, an incorporated therapeutic compound (monosialoganglioside, GM1), is developed for SCI therapy. A low-thoracic hemisection in rats is used as SCI model to evaluate therapeutic efficiency. The GM1-incorporating Poloxamer-407 and 188 polymer solution is conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…For instance, a hydrogel incorporating poloxamer-407/188 polymer and monosialoganglio-side (GM1-hydrogel) was found be effective in preventing cell apoptosis and glial scar formation in rabbit spinal cord injuries (SCI) [60]. Recently, our group prepared a thermosensitive GFs hydrogel system for delivering single GFs directly to the lesion area of damaged nerves [26], which consists of poloxamer 407 and heparin through a poly-condensation reaction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a hydrogel incorporating poloxamer-407/188 polymer and monosialoganglio-side (GM1-hydrogel) was found be effective in preventing cell apoptosis and glial scar formation in rabbit spinal cord injuries (SCI) [60]. Recently, our group prepared a thermosensitive GFs hydrogel system for delivering single GFs directly to the lesion area of damaged nerves [26], which consists of poloxamer 407 and heparin through a poly-condensation reaction.…”
Section: Discussionmentioning
confidence: 99%
“…15,30 In a typical experiment, HP hydrogel exhibited a liquid state in low temperature. After it was locally administered in vivo, a three-dimensional network structure was formed which sustained the drug releasing from the HP hydrogel.…”
mentioning
confidence: 99%
“…However, maintaining the retention and stability of exosomes over time and resist of microenvironment variation in vivo after transplantation is a significant barrio to enhance the therapeutic efficacy in the clinical application of MSC-derived secreta [56,57]. Tan et al [58] demonstrated that therapeutic molecules such as neurotrophin (BDNF) could be effectively encapsulated and delivered to the target tissue of SCI in a sustained manner with retained biological activity via biomaterials, reducing undesirable biological side effects in non-target regions.…”
Section: Secretome Of Mscs and Suppression Of Neuroinflammationmentioning
confidence: 99%